Analisis Pengaruh Kompetensi, Lingkungan Kerja Non Fisik dan Gaya Kepemimpinan terhadap Efektivitas Kerja melalui Motivasi sebagai Variabel Intervening - Lutfi Prajayanti; Kusuma Chandra Kirana; Gendro Wiyono (Universitas Pendidikan Indonesia, 2023)
Education is the spearhead of the progress of a nation, thus the national education system becomes a very important parameter in determining the quality of human resources. Especially in the field of education where the work effectiveness of educators will greatly influence the future of students, for this reason researchers are interested in knowing the extent to which competency, non-physical work environment and leadership style influence work effectiveness through motivation as an intervening variable, besides that besides the contribution of schools that support with complete and best facilities and infrastructure. The population used in this study were teachers at Pangudi Luhur High School in Yogyakarta. The sampling technique used Non Probability Sampling for this type of sampling using saturated sampling with a total sample of 57 respondents. The data analysis method used in this research is descriptive analysis and inferential analysis. The test results show that competence has a positive but not significant effect on motivation, Non-Physical Work Environment has a positive but not significant effect on motivation, Leadership Style has a positive and significant effect on motivation, Competence has a positive and significant effect on work effectiveness, Non-physical work environment has a positive and significant effect on work effectiveness, leadership style has a positive and significant effect on work effectiveness, motivation has no significant positive effect on work effectiveness.